Pengaruh Tanggung Jawab Sosial Terhadap Performa Keuangan Perusahaan Dan Efek Moderasi Dari Struktur Kepemilikan Perusahaan Yang Terdaftar Di Bursa Efek Indonesia Periode 2018-2022 - Triadi, Muhammad Ridwan; Sidjabat, Mona Ridho (Jurnal Manajemen dan Usahawan Indonesia, 2024)
This study investigates the effect between corporate social responsibility (CSR) and corporate financial performance (CFP) and the moderating effect of ownership structure. This study divides ownership structure into ownership concentration and ownership type. Data was taken from Thomson Reuters includes 37 sample companies listed on the Indonesia Stock Exchange for the period 2018-2022. This study uses the least squares regression method (OLS) and the two-stage least squares method (2SLS). The result show a positive and significant effect between CSR and CFP. However, ownership concentration inhibits the positive effect and CSR in non-SOE companies cannot increase CFP better than SOE companies.